Ethnographic Fieldnote Writing: Methodological Challenges in the 21st Century - Adhikari, Debendra Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2018)
This paper focuses on the methodological challenges in the 21st century of ethnographic field note writing using pen and pencil amidst the increasing use of modern gadgets. Many ethnographers have been using modern electronic devices to collect field texts. Thus, the ethnographers are in a dilemma whether to use the traditional field note writing method or the modern method using gadgets. To address the research problem I conducted in-depth interview with 23 participants focusing on Communist Party of Nepal Maoist female ex-combatants and observed their activities for a prolonged period in the natural setting. Fieldnote is considered the most important field text collection method in ethnographic research. Ethnographic research requires more descriptive and interpretive field text analysis with cultural aspects. This article considers the creation of ethnographic fieldnote in the act of seeing and writing through emerging insight and understanding. The challenges related to the method of writing ethnographic fieldnote have received less attention in methodological discussions. This indicates that while writing ethnographic fieldnote in the field may have some benefits looking at the field practicalities but is equally challenging. There are certain methodological aspects involved in every fieldnote writing mission. My personal experiences of writing ethnographic fieldnote about the experiences of the excombatants fail to exclude the researcher in terms of methodological aspects rather it is more multifaceted and inspiring.